PENGARUH STRATEGI MARKETING MIX TERHADAP KEPUTUSAN PEMBELIAN PRODUK SUSU PT. FRISIAN FLAG INDONESIA DI SURABAYA - Novita, Dina (Fakultas Ekonomi Universitas Wisnuwardhana, 2013)
This study aims to mengetahi influence marketing mix strategy on purchasing decisions PT Frisian Flag dairy products in Surabaya. The sample in the study there were 50 people who serve as respondents whereas hypothesis testing is done using multiple linear regression method.The results simultaneously variable product (X1) price (X2), distribution channels (X3) and promotion (X4) has a significant influence on purchasing decisions (Y). It is shown from the test results showed that the F test F count (15.208)> F table (2,806). So the product of independent variables (X1) price (X2), distribution channels (X3) and promotion (X4) influence on purchasing decisions.Partially, the independent variable in this study the variable product (X1) price (X2), distribution channels (X3) and promotion (X4) significantly influence the purchase decision (Y). This is indicated by the value of t count> t table (2.680> 2.014) for the product, (2.878> 2.014) for the price, (2.392> 2.014) for distribution channels and (3.616> 2.014) for promotion. The independent variables that have a dominant influence on purchasing decisions dairy PT Frisian Flag Indonesia in Surabaya is promotion.Keywords: marketing mix, product, price, distribution channels, promotion, purchasing decisions